"Going the extra mile" endangers doctors, patients, and NHS. (26th July 2017) - Moberly, Tom
Abstract : Jan Wise, BMA medicolegal committee chair, tells Tom Moberly that the culture of doctors stretching themselves to work beyond their shifts and cover rota gaps has to end